The Jungle Books - Kipling, Rudyard (Penguin, 2016)
“This is a beautiful book — essential reading for anyone who loves animals and knows how much they can teach us about being human.” ― Gwen Cooper, author of "Homer’s Odyssey: A Fearless Feline Tale, or How I Learned About Love and Life with a Blind Wonder Cat"